2022
DOI: 10.1038/s41467-022-30575-2
|View full text |Cite
|
Sign up to set email alerts
|

High resolution microfluidic assay and probabilistic modeling reveal cooperation between T cells in tumor killing

Abstract: Cytotoxic T cells are important components of natural anti-tumor immunity and are harnessed in tumor immunotherapies. Immune responses to tumors and immune therapy outcomes largely vary among individuals, but very few studies examine the contribution of intrinsic behavior of the T cells to this heterogeneity. Here we show the development of a microfluidic-based in vitro method to track the outcome of antigen-specific T cell activity on many individual cancer spheroids simultaneously at high spatiotemporal reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 45 publications
2
54
0
Order By: Relevance
“…Similar observations of perforin pore-positive but ineffective (nonlethal) CTL-target cell pairings indicate similar multihit interactions in CD19-CAR T cells targeting mouse B cell lymphoma in vivo [18] and CTLs confronted with virally transfected target cells [12]. Furthermore, monitoring CTL killing of tumor spheroids in controlled microfluidic-based systems combined with probabilistic modeling provides evidence of cooperative killing behavior that exceeds purely additive effects of individual T cell activities [19]. Thus, CTL-induced target cell death is not a binary event but rather relies on the integration of damage frequency with damage repair efficacy in the target cell over time.…”
Section: Additive Cytotoxicitymentioning
confidence: 60%
See 1 more Smart Citation
“…Similar observations of perforin pore-positive but ineffective (nonlethal) CTL-target cell pairings indicate similar multihit interactions in CD19-CAR T cells targeting mouse B cell lymphoma in vivo [18] and CTLs confronted with virally transfected target cells [12]. Furthermore, monitoring CTL killing of tumor spheroids in controlled microfluidic-based systems combined with probabilistic modeling provides evidence of cooperative killing behavior that exceeds purely additive effects of individual T cell activities [19]. Thus, CTL-induced target cell death is not a binary event but rather relies on the integration of damage frequency with damage repair efficacy in the target cell over time.…”
Section: Additive Cytotoxicitymentioning
confidence: 60%
“…OPEN ACCESS that enhances local CTL swarming [19], possibly by chemokines produced by CTLs upon target cell recognition [54]. In addition, supramolecular attack particles, which were recently described to be deposited on tumor cells by transient CTL and NK cell contacts [55][56][57], may contribute to the additive cytotoxic effects towards target cells.…”
Section: Trends In Cancermentioning
confidence: 99%
“…IFNg receptor signaling leads to an increase in the production of CXCR3 ligands, namely CXCL9, 10 and 11 which have the potential to promote the avidity of LFA-1 on T cells as well as to attract other immune effector cells to the tumor site. In this context, Using an ex vivo 3D tumor model Ronteix et al (32) have shown that the first T cells contacting tumor cells initiated a positive feedback loop that accelerated the recruitment of other T cells to the tumor spheroid in agreement with the secretion of a T cell-attractant factor.…”
Section: Questions and Conclusionmentioning
confidence: 99%
“…In this context, Using an ex vivo 3D tumor model Ronteix et al. ( 32 ) have shown that the first T cells contacting tumor cells initiated a positive feedback loop that accelerated the recruitment of other T cells to the tumor spheroid in agreement with the secretion of a T cell-attractant factor.…”
Section: Questions and Conclusionmentioning
confidence: 99%
“…Organoids may prove useful for high-throughput chemical screens, but they lack crucial components of the TME and have so far not been extensively validated for melanoma (Ronteix et al, 2022). Testing drug efficacy on ex vivo tumor fragments was recently shown to hold a robust predictive capacity, including for immunotherapy (Voabil et al, 2021).…”
Section: Introductionmentioning
confidence: 99%